(untitled) (Research Journal on Multi-disciplinary Issues, 2026)
Technological change in higher education institutions refers to adopting new systems, processes, and tools to enhance learning, teaching, research, administration, and overall institutional effectiveness. This article examined how technological change is associated with teachers’ job performance based on quality-accredited higher education institutions in Nepal. To conduct this study, a descriptive research design has been adopted. The population consisted of 3900 teaching faculty from 76 quality-accredited higher education institutions in Nepal. A valid sample size comprises 370 teaching faculty, which was chosen from the population using a convenience sampling method. Data collected through a five-point Likert scale structured questionnaire was used to collect the primary data. The findings revealed a positive association between technological changes and job performance of teachers, as technology adoption simplifies tasks, saves time, and significantly boosts employee productivity. Using Information and Communication Technology (ICT) enhances teaching efficiency for educators and improves students’ learning experiences. Therefore, digitizing teaching and learning methods has become essential for improving and strengthening the quality of education. However, a small association between technological changes and job performance indicated that quality-accredited higher education institutions need more technological adoption and improvement. The inferences drawn by this study will be helpful to all the stakeholders, such as the University Grant Commission Nepal, higher education institutions, teachers, and policymakers who are directly or indirectly involved in the reform of higher education.